The bureaucratic governance of China’s public health emergency system: an analysis of one province’s response to COVID-19 - Hao, Chuanjin (2025)
This study examines the organisational structure and governance processes of China’s public health emergency system in response to COVID-19, situated within the broader context of China’s bureaucratic governance mechanisms and operational logic. A qualitative research approach was adopted, focusing on a specific province as a case study. Data sources comprise three years of central and provincial policy documents related to COVID-19, alongside interviews conducted with 19 participants from the selected province, all of whom have official backgrounds. Guided by Pierson’s three dynamics framework, the study investigates power distribution, interest representation, and fiscal arrangements to delineate China’s public health emergency system and its governance processes. The findings reveal dynamic interactions within China’s bureaucratic system, characterised by varying degrees of guidance and leadership across departments, as well as distinct coordination mechanisms between central and provincial governments. These variations are reflected in the governance processes during the pandemic. The study also traces the trajectory of campaign-style governance (yundongshi zhili, 运动式治理) throughout COVID-19, emphasising its initial efficiency followed by subsequent dysfunction. This is evidenced by the limited effectiveness of leadership small groups (lingdao xiaozu, 领导小组) and cadre downshifting. Despite a top-down emphasis on achieving zero-COVID targets, local governance exhibited considerable flexibility, with bureaucrats adopting a muddling through (de guo qie guo, 得过且过) approach. Moreover, amid an increasing centralisation of fiscal power and growing local reliance on central transfers, local officials actively sought alternative financial support. These governance phenomena during China’s COVID-19 response highlight an inherent tension between decision-making conformity and governance effectiveness within the Chinese bureaucratic system. Informal mechanisms, such as guanxi (关系, meaning social relations), serve to alleviate this tension but do not provide a fundamental solution. Consequently, this study advocates for a reduction in the governance burden on the authoritative government by fostering greater participation from social organisations and private enterprises in future public health emergency governance.